PENGARUH KADAR HEMOGLOBIN DAN KEBUGARAN JASMANI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PENJASORKES) - Agung Cahyadi (Performa, 2021)
This study was based on the problem found among the students of SMAN 2 Padang related to the low learning outcomes in Physical Education, sport and health course. These learning outcomes were affected by hemoglobin levels and physical fitness. This study aims to identify the direct and indirect effects among the variables hemoglobin levels, and physical fitness towards learning outcomes in Physical Education, sport and health course. Quantitative research method with Path Analysis approach was carried out in this study. The study involved 308 (all) male students of SMAN 2 Padang in academic year 2018-2019 as the population. 100 students were taken as the sample by using Proportional Stratified Random Sampling. The data were collected using Hb test meter for hemoglobin levels; physical fitness test for physcal fitness; and the first semester exam results for learning outcomes. The results of data analysis show that the learning outcomes in Physical Education, sport and health course were: (1) affected directly by hemoglobin levels for 5.34%, (2) physical fitness for 13.40%; (2) affected indirectly by hemoglobin levels and physical fitness for 12.9%,